Robot Keseimbangan Beroda Dua dengan Sistem Kontrol Keseimbangan dan Posisi Menggunakan Metode PID Bertingkat - Niam Tamami; Ibrahim Muhammad Diin; Bambang Sumantri; Endra Pitowarno (Jurnal Rekayasa Elektrika, 2018)
The two-wheeled balancing robot is a robot that will maintain its balance to stay upright by using two wheels. This robot cannot be stable when the condition is upright and requires a control mechanism when moving. There are at least two control mechanisms in this robot, first is balance control, and the second is position control. The cascade PID method is proposed as a control mechanism, which consists of balance control as primary control and position control (distance and direction) as a secondary control. This method has been applied to robots. Based on the first, second, and third experiment, the best configuration of cascade PID control is PID for the balance control block, PD for distance control, and PD for direction control. By using cascade PID control, the two-wheeled balancing robot has been able to balance itself with oscillations ranging from ± 15.00 degrees when moving and it can move towards the ordered position with the error position from the target. Fourth experiment position error is (0.17, -0.26) and (0.45, -0.43) for the fifth experiment.